2017
DOI: 10.15414/jmbfs.2017.6.6.1309-1313
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Isolation of Peptide Metabolites of an Antifungal Bacterial Isolate Identified as Bacillus Amyloliquefaciens Subspecies Plantarum Strain Fzb42

Abstract: Some bacteria produce antimicrobial chemicals in their immediate environments. These antimicrobial agents are enzymes, polypeptides or non-protein organic compounds. In this study, a bacterial isolate that produces antifungal chemical(s) was isolated from an over incubated nutrient agar plate that was exposed to air. The bacterium is aerobic, Gram positive bacilli; capsule and endospore producing. It ferments glucose and sucrose but not lactose, galactose, mannitol and sorbitol; it is citrate, indole, methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Targeted interaction assays with the environmental isolates nearest the antibiotic-producing isolate established that the isolate (Paracoccus sp., strain CA-113-2) to the left of the antibiotic producer (Streptomyces sp., strain CC-108-1) was not stimulating antibiotic production by the antibiotic-producing isolate (c, i), but rather that the yellow isolate to the right of the antibiotic-producer (Agrococcus sp., strain CA-87-1) was responsible for impairing its ability to inhibit MRSA growth (c, iii). The antibioticproducing isolate also affected the growth of a lawn of the marine bacterium Bacillus oceanisediminus (d) of spectroscopic data to data previously reported for diketopiperazines in the literature, including HRMS and comparison of NMR 1 H and 13 C chemical shifts, supported structural assignments of cyclo(Leu-Pro), cyclo(Phe-Pro), and cyclo(Gly-Pro) [37][38][39][40]. Additional NMR data, including H-H couplings via COSY and C-H couplings via HSQC and HMBC, were used to further confirm the structural assignment.…”
Section: Resultssupporting
confidence: 72%
“…Targeted interaction assays with the environmental isolates nearest the antibiotic-producing isolate established that the isolate (Paracoccus sp., strain CA-113-2) to the left of the antibiotic producer (Streptomyces sp., strain CC-108-1) was not stimulating antibiotic production by the antibiotic-producing isolate (c, i), but rather that the yellow isolate to the right of the antibiotic-producer (Agrococcus sp., strain CA-87-1) was responsible for impairing its ability to inhibit MRSA growth (c, iii). The antibioticproducing isolate also affected the growth of a lawn of the marine bacterium Bacillus oceanisediminus (d) of spectroscopic data to data previously reported for diketopiperazines in the literature, including HRMS and comparison of NMR 1 H and 13 C chemical shifts, supported structural assignments of cyclo(Leu-Pro), cyclo(Phe-Pro), and cyclo(Gly-Pro) [37][38][39][40]. Additional NMR data, including H-H couplings via COSY and C-H couplings via HSQC and HMBC, were used to further confirm the structural assignment.…”
Section: Resultssupporting
confidence: 72%
“…Bacillus amyloliquefaciens also, have been reported as both plant growth promoters and biocontrol agents against soilborne pathogens including Fusarium wilt of banana and potato dry rot caused by Fusarium sp. 45 . In our study 20 isolates showed both plant growth promotors and biological controls against P. capsici.…”
Section: Discussionmentioning
confidence: 99%
“…B. amyloliquefaciens and B. velezensis have been widely reported as plant growth promoters and biocontrol agents against a broad range of soil-borne pathogens including Fusarium wilt of banana and potato dry rot caused by Fusarium sp. ( Recep et al, 2009 ; Wang et al, 2013 ; Xu et al, 2013 ; Meng et al, 2016 ; Adibi et al, 2017 ). A recent study showed that B. velezensis had a broad-spectrum biocontrol activity via antagonism against two foliar bacterial pathogens and soil-borne fungal pathogens ( Liu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%